Ozonation of recalcitrant O-isopropyl-N-ethylthionocarbamate catalyzed by galena in flotation effluents and its dissolution behaviors. (1st May 2021) - Fu, Pingfeng; Wang, Lianghua; Lin, Xiaofeng; Ma, Yanhong; Hou, Zongwu
Graphical abstract: Highlights: Ozonation of O -isopropyl- N -ethylthionocarbamate was enhanced by galena. The galena addition reduced the ozone consumption remarkably. Hydroxyl radicals were generated via catalytic ozone decomposition on galena. The dissolution of galena was accelerated significantly by adding ozone. The galena was readily oxidized by oxidants (e.g., ozone and hydroxyl radicals). Abstract: Little attention has been paid to the catalytic effects of sulfide minerals and their dissolution behaviors in treating flotation effluents by advanced oxidation processes (AOPs). In this work, the improved ozonation of recalcitrant O -isopropyl- N -ethylthionocarbamate (IPETC) collector by adding galena was investigated with the disclosure of galena dissolution. The removal efficiency of IPETC and its mineralization was compared by sole ozonation and galena catalytic ozonation. The galena dissolution process was examined by determining Pb(II) concentrations and analyzing galena surface with X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectroscopy. The galena had remarkably increased the IPETC removal and promoted its mineralization by the ozonation. Simultaneously, the ozone consumption could be significantly reduced. The catalytic decomposition of ozone on galena surface resulted in the yield of more hydroxyl radicals, leading to the enhanced removal of IPETC. The released Pb(II) concentrations were as high as 14.9–23.2 mg/L after the ozonation, indicating the significant dissolution of galena. The XPS and FTIR analysis confirmed the formation of lead oxides with high solubility after the oxidation of galena. The negative impacts of releasing toxic heavy metals from sulfide minerals were discussed while the flotation effluents were treated by the AOPs.